2015
DOI: 10.3136/fstr.21.765
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential and α-galactosides Content of Unhulled Seeds of Dark Common Beans Subjected to Tempe-type Fermentation with <i>Rhizopus microsporus</i> var. <i>chinensis</i> and <i>Lactobacillus plantarum</i>

Abstract: in tempe was 67%, 53% and 57% lower, respectively.Keywords: tempe, antioxidants, phenols, α-galactosides, common beans, processing IntroductionCommon bean (Phaseolus vulgaris) is consumed worldwide as rich and inexpensive source of protein, dietary fibers, vitamins and minerals. Dark common bean is also considered functional food (Vadivel et al., 2011) due to the high level of phenolic compounds present in the seed coat (Boateng et al., 2008).However, processes usually applied in order to prepare dry beans for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
2
7
1
Order By: Relevance
“…The enzyme complex could also have a hydrolyzing effect on tannins. The results agree with those reported by Starzyńska‐Janiszewska, Stodolak, and Wikiera (), they obtained a reduction of 85.9% on tannins content from water‐soaked and cooked common beans.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The enzyme complex could also have a hydrolyzing effect on tannins. The results agree with those reported by Starzyńska‐Janiszewska, Stodolak, and Wikiera (), they obtained a reduction of 85.9% on tannins content from water‐soaked and cooked common beans.…”
Section: Resultssupporting
confidence: 92%
“…This tendency is different for the results obtained by Piecyk et al () of 25.7% on autoclaved Raba beans. The flavonoids level did not decrease ( p > .05) with any of the processes, which is consistent with the results from Starzyńska‐Janiszewska et al (), where there was a minimum reduction of flavonoids (6.9%). On the anthocyanins content, the levels were nondetectable after treatments for both beans (Table ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Generally, thermal processing methods, such as cooking and steaming, cause a significant decrease in antioxidant activity (Table ). For instance, Starzyńska‐Janiszewska, Stodolak, and Wikiera () reported that soaking and cooking significantly reduced the free radical scavenging activity and reducing power of common beans. Chen et al.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Generally, thermal processing methods, such as cooking and steaming, cause a significant decrease in antioxidant activity (Table 5). For instance, Starzyńska-Janiszewska, Stodolak, and Wikiera (2015) reported that soaking and cooking significantly reduced the free radical scavenging activity and reducing power of C 2018 Institute of Food Technologists ® Vol. 17, 2018 r Comprehensive Reviews in Food Science and Food Safety 1533 Abbreviations, TOSC, total oxyradical scavenging capacity; VCE, vitamin C equivalent; TEAC, Trolox equivalent antioxidant activity; TE, Trolox equivalent; ABTS, 2, 2 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) free radical scavenging assay; DPPH, 1, 1-diphenyl-2-picrylhydrazyl free radical scavenging assay; OH, hydroxyl radical absorbance capacity; ORAC, oxygen radical absorbance capacity; LPI, lipid peroxidation inhibition; OH, hydroxyl free radical scavenging assay; FRAP, ferric reducing antioxidant potential assay; RP, reducing power.…”
Section: Antioxidant Activitymentioning
confidence: 99%